2019
DOI: 10.1590/1516-4446-2018-0054
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal behavior among substance users: data from the Second Brazilian National Alcohol and Drug Survey (II BNADS)

Abstract: Objective:To investigate the prevalence rates of suicidal ideation (SI) and suicide attempts (SA) and their association with substance use in a nationally representative sample of Brazilians.Methods:The Second Brazilian National Alcohol and Drug Survey (II BNADS) is a household cross-sectional survey that investigated the consumption of psychotropic drugs and associated risk factors. This national probability sample survey used a multistage cluster design to select 4,607 participants aged 14 or older and had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 12 publications
(13 reference statements)
4
25
0
3
Order By: Relevance
“…In this study, the 12 months prevalence of suicidal behavior was found to be 41.4% (95% CI: 38.2, 44.9) among residents with problematic substance use in South Gondar zone, northwest Ethiopia. This finding was relatively consistent with a study done among people with drug addiction problems in Brazil, 43.9% and a study done in Frankfurt, Germany, 41% [10,26]. However, the current finding was lower than among those studies conducted in Saudi Arabia and US, where suicidal behavior was reported by 50.7 and 50.1% of people with substance misuse respectively [15,17].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the 12 months prevalence of suicidal behavior was found to be 41.4% (95% CI: 38.2, 44.9) among residents with problematic substance use in South Gondar zone, northwest Ethiopia. This finding was relatively consistent with a study done among people with drug addiction problems in Brazil, 43.9% and a study done in Frankfurt, Germany, 41% [10,26]. However, the current finding was lower than among those studies conducted in Saudi Arabia and US, where suicidal behavior was reported by 50.7 and 50.1% of people with substance misuse respectively [15,17].…”
Section: Discussionsupporting
confidence: 91%
“…From participants with problematic substance use in USA, 34.1% of them attempt suicide at least once whereas comorbid depression was increased the odds of suicidal attempt [9]. Among people with drug addiction in Brazil, 43.9% of drug users had history of suicidal behavior and depressive symptoms, family history of suicide, maternal psychiatric history and smoking were associated with suicidal ideation and attempt [10,11]. Suicidal behavior reported in 37.6% of participants who had alcohol dependence and in 29.5% of participants who had other drug dependence in USA [12].…”
Section: Introductionmentioning
confidence: 99%
“…We did not find any studies that examined CDs or individuals with other substance use disorders versus a control group. Nevertheless, cocaine misuse is a known risk factor for suicidal ideation and suicide attempts (Abdalla et al, ; Bohnert et al, ; Pavarin & Fioritti, ). Moreover, CDs showed elevated depression and lower self‐esteem, relative to HCs.…”
Section: Discussionmentioning
confidence: 99%
“…Substance misuse is associated with an increased risk for suicide (Abdalla et al, ; Bohnert, Ilgen, Louzon, McCarthy, & Katz, ; Pavarin & Fioritti, ). Data from the Veterans Health Affairs revealed an elevated risk for suicide for all substance use disorders (Bohnert et al, ).…”
mentioning
confidence: 99%
“…A recently large-scale study with a representative sample of Brazilians found rates of suicidal attempts and deaths in the general population of 9.9 and 5.4%, respectively. In crack-cocaine users these rates were significantly higher, 40.0 and 20.8%, respectively [13]. Previous studies have shown that 47% of crack-cocaine users had a current suicide risk [14], and a prevalence of suicidal behaviors of 30% in crack-cocaine addicts, in Brazil.…”
Section: Introductionmentioning
confidence: 89%